Superficial neoplasia involving the Ileocecal valve: Clinical outcomes of endoscopic submucosal dissection. Issue 7 (July 2021) - Andrisani, Gianluca; Fukuchi, Takehide; Antonelli, Giulio; Hamanaka, Jun; Hassan, Cesare; Costamagna, Guido; Maeda, Shin; Di Matteo, Francesco Maria; Hirasawa, Kingo
Abstract: Background: Endoscopic submucosal dissection (ESD) is the treatment of choice for colorectal superficial neoplasia, but certain anatomical locations are challenging even for skilled endoscopists. Ileocecal valve (ICV) is considered a technically challenging site for ESD. Objective: Aim of this study was to analyze efficacy and safety of Endoscopic Submucosal Dissection in the treatment of colorectal neoplasia involving the ileocecal valve (ICV) Design: Retrospective study. Patients: We retrospectively evaluated 1507 consecutive patients undergoing ESD at two tertiary referral centres for ESD (Italy and Japan) from January 2008 to March 2020. Main Outcome Measures: Demographic, clinical, procedural, and follow-up data was collected, analysed, and compared between patients with ileocecal valve lesions (ICVL) and patients with non-ICVL. Results: Overall, 1507 patients were enrolled (872 M, 57.8%), of these 53 patients had lesions involving the ICV. Mean age was 70.2 years (range, 53–83 years). En-bloc resection was achieved in 52 (98%) patients. The median specimen size of ICVL was 36.4 mm (range, 8–80 mm), significantly smaller than non-ICVL ( p  = 0.005). Procedure time was significantly longer in the ICVL group, (71.3 vs. 58.9 min; p  = 0.03). Non Granular Type Laterally Spreading Tumors (LST-NG) were significantly more frequent in the ICVL group compared to rectum (52.8% vs. 25.7; p  = 0.0001). En-bloc resection rate in the ileocecal region did not differ significantly between groups ( p  = 0.20). Complications such as perforation and postoperative occurred respectively in 3/53 (5.7%) and 1/53 (2%) patient, and were treated conservatively. At first surveillance colonoscopy performed at 6 months, recurrent adenoma was detected in 2/53 patients (3.9%). Conclusions: ESD is safe and effective for the treatment of colorectal neoplasia involving the ileocecal valve if performed by expert endoscopist in referral centres.